Pengaruh Kenerja Keuangan dan Strategi Manajemen Laba dalam Meningkatkan Nilai Perusahaan (Analisis Empiris Kinerja Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia: Perspektif 2019-2023) - Fiqran Pratama, Rizky; Alhadi, Irgi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study examines the impact of financial performance and earnings management on firm value in the manufacturing sector listed on the Indonesia Stock Exchange during the period of 2019 to 2023. Financial performance is measured using the Return on Assets (ROA) ratio, while earnings management is assessed through discretionary accruals calculated using the Modified Jones model. Firm value is measured using the Price to Book Value (PBV) and Price Earnings Ratio (PER). Using multiple linear regression analysis, the results show that financial performance significantly affects firm value, both based on PBV and PER. In contrast, earnings management does not have a significant impact on firm value in both ratios. The study also indicates that while earnings management can influence market perceptions in the short term, excessive earnings management practices can undermine financial statement credibility and reduce investor trust. Strong financial performance, reflected in high ROA ratios, is more dominant in enhancing firm value. Therefore, companies are advised to focus on transparent and effective financial performance management to attract investors and improve competitive positioning in the market.